2020
DOI: 10.1177/1945892420929265
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Odontogenic Rhinosinusitis: Optimization of Surgical Treatment Indications

Abstract: Background The treatment of chronic odontogenic and nonodontogenic rhinosinusitis is different. It requires the elimination of odontogenic cause and optimal sinus surgical treatment. To date, there are no clear indications when sinus surgical treatment is necessary. Objective Our aim was to define clear indication(s) for sinus surgical treatment in patients with chronic odontogenic rhinosinusitis after elimination of odontogenic cause. Methods A group of 96 patients with chronic odontogenic rhinosinusitis caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…ODS has received significantly less attention in the literature compared to rhinosinusitis, and no formalized diagnostic criteria have been established. 17 ODS treatment and outcomes are very different from rhinosinusitis, 10,11,[32][33][34][35][36] and the diagnostic approach to ODS should also be different. Until higher levels of evidence allow for validated ODS diagnostic criteria, this international multidisciplinary CCS serves as a valuable segue to such criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ODS has received significantly less attention in the literature compared to rhinosinusitis, and no formalized diagnostic criteria have been established. 17 ODS treatment and outcomes are very different from rhinosinusitis, 10,11,[32][33][34][35][36] and the diagnostic approach to ODS should also be different. Until higher levels of evidence allow for validated ODS diagnostic criteria, this international multidisciplinary CCS serves as a valuable segue to such criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Although treatment outcomes are highly successful when both the dental source and sinusitis are treated, 10,11,[32][33][34][35][36] if otolaryngologists miss the dental source or dental providers miss the sinusitis, patients may suffer unnecessarily from ongoing dental or sinonasal symptoms. This highlights the importance of otolaryngologists and dental providers being able to suspect ODS based on clinical features, as described earlier in the Suspecting ODS subsection, additionally to otolaryngologists confirming the sinusitis and dental providers confirming the maxillary dental pathology (Fig.…”
Section: 4mentioning
confidence: 99%
“…11 In addition, it has been reported that extraction of causative tooth is an effective treatment of chronic odontogenic sinusitis caused by apical periodontitis. 16 We used a combination of otorhinolaryngological and dental treatment for patients with sinusitis and apical lesions. We performed surgery after conservative treatment, if the outcome was thought to be poor.…”
Section: Discussionmentioning
confidence: 99%
“…While RCTx has been used successfully for ODS, it has only been reported in case reports, 39,40 or small series, 14,41,42 and success rates cannot be determined. The average published success rate for primary dental extraction for ODS due to AP is about 60% 32,42–45 . However, this success rate should be viewed with caution for multiple reasons.…”
Section: Managing Odsmentioning
confidence: 99%